(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Sangli district is the part of south-western Maharashtra. It is one of the developing districts and agriculture is backbone of the district economy. The rural mass of the district is heavily depends on the agriculture and allied activities for their livelihood sources. The majority of the district area is frequently suffers from the drought conditions. The eastern part of the district is often facing the issue of water scarcity and water shortage for both agriculture and domestic uses purpose. The significant industrial development of the district is only observed in western and central part of the district. The MGNREGP is the anti poverty weapon which provides 100 days guaranteed employment to the unskilled rural workforce. In fact MGNREGP is main livelihood source of the rural people in the drought hit area of the Sangli district. Through the MGNREGP, there are several works completed in the district and in progress. The community development works, traditional water bodies renovation work, social forestry, farm roads, farm ponds, rural connectivity, and environmental resources conservation works are either completed or being in progress since last decade. Under this backdrop, the present research study has examined the progress of MGNREGP in Sangli district based on block level secondary data. The study has covered the three year period. The physical and financial progress of the MGNREGP has assessed and attempts are made to examine the trends therein. The study is analytical in nature and it has arrived at conclusion that MGNREGP has significantly grown up in the district during the period under consideration and it has providing employment to rural unskilled workforce. It is also revealed from the study that the out of total 21.08 lakh rural population of the Sangli district, 5.44 lakh people (i.e 25.80 percent) are engaged in MGNREGP. However, at present the active numbers of workers are seen only 0.67 lakh. The proportion of SC workers is also seen significant in total MGNREGP workforce. Thus programme is not only playing significant role in rural development of Sangli district but in upliftment of the weaker segment of the society.